A dispersive liquid-liquid microextraction method for determination of bongkrekic acid in plasma by LC-MS/MS. Issue 5 (3rd April 2021) - Xu, Xiumin; Fang, Lei; Lv, Fen; Liu, Rui; Huang, Xiangdong; Huang, Weixiong; Long, Chaoyang
Abstract: In this study, we describe a dispersive liquid-liquid microextraction strategy for bongkrekic acid (BA) purification, enrichment, and liquid chromatography coupled with mass spectrometry (LC-MS/MS) analysis. Bongkrekic acid (BA) was an important toxin that could cause liver and kidney damages, or even death. Furthermore, there were several food poisoning incidents occurred by BA in many countries including Indonesia, China, and so on. A rapid, simple and reliable determination of BA in plasma was of great value in the clinical diagnosis and treatment of poisoning patients. In this study, we describe a dispersive liquid-liquid microextraction strategy for purification and enrichment of BA followed by liquid chromatography tandem mass spectrometry (LC-MS/MS). The BA (pKa value was 4.15) in the plasma samples were dispersed and extracted by methanol, dichloromethane and 0.1% phosphoric acid solution successively, in which the proper ratios and the dosages were all optimized in this study. The conditions for ionization source and the extracting conditions for BA were also optimized. The matrix effect ranged from 95.0% to 102%, indicating matrix effects may be negligible. The feasibility of the extraction method was tested by analysis of BA in plasma samples. The mean recoveries for BA determination were achieved between 88.3% and 98.4%. The LOD and LLOQ for BA were 3.7 and 10 µg L −1, respectively. The proposed method is fast and simple, and highly sensitive for testing BA in plasma. Graphical Abstract: UF0001